Vertical Distribution and Variability of Available Nutrients in Southern Mango-Supporting Belts of Karnataka - Kaushik Saha,; K.S. Anil Kumar,; Jagdish Prasad, (Journal of the Indian Society of Soil Science, 2024)
The nutrient inadequacy and/or nutrient mining owing to intensive cultivation warrants for delineation of spatial and vertical distribution of essential nutrients for sustainable yield management. The objective of the present study was to evaluate the relationship between soil characteristics and the vertical distribution of the nutrients in southern mango belts (SMB) of Karnataka. Nine major taluks (Magadhi, Ramanagara, Gubbi, Tumkur, Bangalore North, Hoskote, Chintamani, Mulabaghilu, and Srinivasapura) were selected on the basis of area and production of mango. Data indicated deficiency of nitrogen throughout the profiles of study areas, and in general availability of primary nutrients decreased with depth. Ramanagara, Tumkur, and Gubbi had adequate available phosphorus, while Mulabaghilu, Srinivasapura, and Magadhi soils were found to be deficient. Exchangeable calcium and magnesium in soils were found to be sufficient thoughout the mango-supporting track of study area. Ramanagara Taluk under southern dry zone (SDz) had maximum concentration of micronutrients but their deficiencies were found in Ultisols of Gubbi and Tumkur along with Mulabaghilu taluk. Correlation analysis revealed that soil pH had the significant negative correlation (p